Manajemen Laba, Profitabilitas, dan Likuiditas sebagai Peringkat Obligasi - Ulya Anisa’ul Maghfiroh; - Fidiana (Jurnal Riset dan Aplikasi: Akuntansi dan Manajemen, 2023)
Abstract The purpose of the study is to test the influence of earnings management, profitability, and liquidity to the bond rating. By purposive sampling method, we used 11 manufacturing companies that listed in the Indonesia Stock Exchange (IDX) during the 2013-2016 period and rated by PT Pefindo as sample. Hypothesis testing uses logistic regression analysis to test the influence of earnings management, profitability, and liquidiy to bond rating. The results of this research proved that the variable of earnings management and liquidity does not influenced the rating of bonds. While the profitability variables give influence the rating of bonds.